HUBUNGAN ANTARA JARAK, TINGGI SIKU DENGAN TEMPAT DUDUK DAN KELUHAN MOSCULOSKELETAL PADA PEKERJA BAGIAN JUMBO BAG DI PERUSAHAAN PRODUKSI PLASTIK TAHUN 2013 - Doni Dwi Kristanto; Demes Nurmayanti; Ferry Kriswandana (GEMA LINGKUNGAN KESEHATAN, 2014)
Sewing machine operators are at high risk of developing musculoskeletal disorders due toworking in seated position at poorly designed workstations, performing the same operation during theentire course of the workday. The poor postures resulting from these conditions, combined with highlyrepetitive and time-pressured work may result in high incidence of work-related musculoskeletal disordersamong sewing machine operators. The main objective of this study was to analyze the relationshipbetween the distance from elbows to seat pan and musculoskeletal complaints among sewing machineoperators in a plastic manufacturing company.This is ananalytical research using cross sectional approach. The total number of subjects understudy were 74 subjects out of a total of 286 workers drawn by random sampling.The study discovered that respondents were subjected to not ergonomics elbow position as manyas 89.6 %, with mild complaints 50 % and serious complaints was 50 %. The chi square test proved thatthere was a relationship between the distance of elbow to the seat with mosculoskeletal complaints.The result of this study concluded that musculoskeletal complaints are prevalent among sewingworkers. Therefore, it is recommended that the company should provide adjustable chairs, allow frequentshort breaks and adequate work spaces to all workers in order to reduce future musculoskeletalcomplaints.